Accessing Healthcare Services During the COVID-19 Pandemic: The Plight of Sexual Assault Survivors. Issue 2 (8th April 2021) - Munro-Kramer, Michelle L.; Cannon, Lindsay M.; Scheiman, Lisa; St Ivany, Amanda R.; Bailey, Joanne M.
ABSTRACT: Introduction: Despite a global focus on intimate partner violence during the COVID-19 pandemic, there has been little exploration into how the pandemic and its associated restrictions have impacted sexual assault survivors and their ability to access specialized care and resources. The purpose of this research brief is to use longitudinal data to compare the number of medical forensic examinations done seasonally prepandemic and during the COVID-19 pandemic shelter-in-place order. Methods: This analysis uses retrospective data on medical forensic examinations from January 2010 through November 2020 from one large academic Midwestern hospital. Results: Results show that monthly medical forensic examinations have increased over time, from a mean of 4.5 cases per month (range: 1–9) in 2010 to a mean of 9 cases per month (range: 7–11) in 2019. In April 2020, when COVID-19-related shutdowns were at their first peak, cases dropped to a historic low of 0 examinations (the lowest number of cases in the past 10 years). Conclusions: The data show an initial drop in the number of survivors seeking postassault care after the COVID shutdown; however, cases rebounded through the second full month of shutdown orders. Programs that provide medical forensic examinations need to be prepared for subsequent waves of survivors, who may be COVID-19 positive. We must be better prepared for many of the adverse consequences impacting individuals around the country related to COVID-19 responses.